The Effect Of The Combination Of Rooming-In And Oxytocin Massage On Breast Milk Production During The First 24 Hours Post Cesarean Section At Rs Pelita Insani Martapura - Pebia Norviana; Sunartono Sunartono; Siti Maimunah; Istri Yuliani; Hargianti Dini Iswandar (Universitas Pahlawan Tuanku Tambusai, 2026)
Breast milk is the optimal nutrition for newborns. However, mothers undergoing cesarean section often experience delayed lactation due to anesthesia effects, surgical pain, stress, and postponed mother–infant contact. Non-pharmacological interventions such as rooming-in and oxytocin massage have been shown to improve lactation, but studies combining these two methods remain limited. Objective this study is to analyze the effect of combining rooming-in and oxytocin massage on breast milk production during the first 24 hours post-cesarean section. This study applied a quasi-experimental design with a pre-post test control group approach. The sample consisted of 24 post-cesarean mothers at Pelita Insani Hospital, Martapura, divided into intervention (rooming-in + oxytocin massage) and control (standard care) groups. Outcomes measured were colostrum volume, onset of lactation, and frequency of let-down reflex. Data analysis was performed using t-test, Mann-Whitney, and ANCOVA to control confounding variables, with a significance level of p<0.05.The combination of rooming-in and oxytocin massage significantly increased milk volume (38.7±6.4 ml vs 23.4±5.1 ml; p<0.001), accelerated lactation onset (8.4±2.1 hours vs 14.7±3.4 hours; p<0.001), and improved let-down reflex frequency (6.8±1.5 times vs 3.9±1.2 times; p<0.001) compared to the control group.Rooming-in combined with oxytocin massage is an effective and safe evidence-based intervention to enhance early milk production in post-cesarean mothers within the first 24 hours, supporting exclusive breastfeeding success.